Groundwater salinization in northwestern Germany: A case of anticipatory governance in the field of climate adaptation? - Leena Karrasch; Bernd Siebenhüner; Stephan L. Seibert (Earth System Governance, 2023)
Groundwater salinization due to sea-level rise is a problem that governance actors in coastal areas of the North Sea region have overseen for a long period. As an ecological problem associated with climate change, it can be severely exacerbated by careless water management. This paper studies governance processes, actor perspectives and responses to groundwater salinization and sea-level rise in the East Frisian and Frisian regions of the German North Sea coast. Due to its low-lying landscape, large areas of land remain below sea-level, making groundwater salinization an urgent concern. Our research questions are: (i) What type of anticipatory governance approach can be found with actors in the study region concerning groundwater salinization and climate adaptation challenges? (ii) How can an alternative anticipatory governance approach promote proactive governance processes addressing the complex problem of groundwater salinization in terms of awareness, preparedness, methods, strategies and policy actions? We conducted semi-structured interviews and workshops between 2017 and 2021, including a group of 15 actors from private and civil society organizations as well as authorities on municipal, inter-municipal and state levels. Our study finds that problem awareness in municipalities and regional governance levels in East Frisia and Frisia is low. Current management of groundwater salinization mainly focuses on technical response measures, while precautionary measures are given low priorities. With regard to governance approaches, our study identifies apparent societal challenges of groundwater salinization at the complex interface between water management, human activities and natural processes, and sustainable ways to manage and protect groundwater resources. However, we found indication for a defensive anticipatory governance approach prioritizing risk management and assessing plausible futures. In participatory processes, we discussed possible technical, non-technical and institutional adaptation options for future implementation. Finally, conclusions will be drawn on how knowledge and awareness building can contribute to change actors perspectives on the overseen problem of groundwater salinization and increase adaptiveness.